2014
DOI: 10.1039/c4cp01543f
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfers in a TiO2-containing MOR zeolite: synthesis of the nanoassemblies and application using a probe chromophore molecule

Abstract: New assemblies constituted by a microporous matrix of mordenite (MOR) zeolite on which TiO2 nanoclusters are deposited were synthesized using ionic oxalate complexes and TiCl3 titanium precursors. The samples were used to investigate the transfer of electrons produced by spontaneous or photo-induced ionization of a guest molecule (t-stilbene, t-St) occluded in the porous volume towards the conduction band of a conductive material placed nearby, in the pores or at least close to their entrance. The reaction mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 102 publications
1
15
0
Order By: Relevance
“…ln C/Co= -kobs t (13) where: co and c are initial dye concentration and the concentration at the moment t and kobs is the overall observed pseudo first-order degradation rate constant.…”
Section: Kinetics Modeling Of the Photocatalysis Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…ln C/Co= -kobs t (13) where: co and c are initial dye concentration and the concentration at the moment t and kobs is the overall observed pseudo first-order degradation rate constant.…”
Section: Kinetics Modeling Of the Photocatalysis Processesmentioning
confidence: 99%
“…One of the shortcomings of this procedure is the difficulty to separate the liquid and the solid photocatalyst after removing the pollutants. For this reason, the researchers have been explored many solid substrate [11][12][13] to immobilize WO3, TiO2 [14]. Thus, FA, by its composition (especially SiO2, Al2O3 and unburned carbon) could be a suitable support material to be optimized as an adsorbent with potential photo-catalytic properties (depending on the burned coal source and composition, small quantities of TiO2, MnO2 can be found in FA).…”
Section: Introductionmentioning
confidence: 99%
“…In a first approach, TiO 2 nanoclusters were synthesized directly within the porous network and electron transfer mechanisms were investigated after photoionization of the adsorbed molecule. 41 The results showed that the presence of the semiconductor within the channels slowed considerably the electron transfers after ionization. However, even if this result is consistent with a possible transfer of electrons to the conduction band of TiO 2 , the yield of this reaction was found to be limited because of the diffusion of TiO 2 nanoclusters to the pore entry and aggregate formation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To take advantage of these persistent charge-separated states, the following stage would be, for instance, to transfer the unpaired electrons to semiconductor materials present nearby. In a first approach, TiO 2 nanoclusters were synthesized directly within the porous network and electron transfer mechanisms were investigated after photoionization of the adsorbed molecule . The results showed that the presence of the semiconductor within the channels slowed considerably the electron transfers after ionization.…”
Section: Introductionmentioning
confidence: 99%
“…One of the shortcomings of this procedure is the difficulty to separate the liquid and the solid photocatalyst after removing the pollutants. For this reason, researchers have explored many solid substrates [17][18][19] to immobilize WO 3 and TiO 2 [20]. Thus, FA, given its composition (especially SiO 2 , Al 2 O 3 and unburned carbon), could be a suitable support material to be optimized as an adsorbent with potential photocatalytic properties depending on the burned coal source and composition, as small quantities of TiO 2 , MnO 2 can be found in FA.…”
Section: Introductionmentioning
confidence: 99%